When There Is Fear, There Is Art: An Interview with Essa Omer. (1st January 2018) - Omer, Essa; Abdullah, Meriwan
Abstract : Meriwan Abdullah interviews Kurdish artist Essa Omer about his most recent work and the significance of the emotion of fear in producing art work.